2017
DOI: 10.1371/journal.ppat.1006471
|View full text |Cite
|
Sign up to set email alerts
|

Cross-modulation of pathogen-specific pathways enhances malnutrition during enteric co-infection with Giardia lamblia and enteroaggregative Escherichia coli

Abstract: Diverse enteropathogen exposures associate with childhood malnutrition. To elucidate mechanistic pathways whereby enteric microbes interact during malnutrition, we used protein deficiency in mice to develop a new model of co-enteropathogen enteropathy. Focusing on common enteropathogens in malnourished children, Giardia lamblia and enteroaggregative Escherichia coli (EAEC), we provide new insights into intersecting pathogen-specific mechanisms that enhance malnutrition. We show for the first time that during p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 78 publications
(134 reference statements)
7
85
0
1
Order By: Relevance
“…As nutrient malnourishment and Giardia infection in humans both likely contribute to decreased immune function [29], a recent report has examined the effects of protein malnourishment on murine Giardia infections. Mice fed a protein deficient diet presented with persistent infections, an alteration in the composition of duodenal microbes, and enhanced growth (weight) impairment when infected with Giardia [30]. Taken together, these reports suggest that Giardia have significant interactions with the intestinal microbiota, which may lead to changes in infection outcome and immunopathology.…”
Section: Giardia Interactions With Intestinal Commensal Microbiotamentioning
confidence: 99%
See 2 more Smart Citations
“…As nutrient malnourishment and Giardia infection in humans both likely contribute to decreased immune function [29], a recent report has examined the effects of protein malnourishment on murine Giardia infections. Mice fed a protein deficient diet presented with persistent infections, an alteration in the composition of duodenal microbes, and enhanced growth (weight) impairment when infected with Giardia [30]. Taken together, these reports suggest that Giardia have significant interactions with the intestinal microbiota, which may lead to changes in infection outcome and immunopathology.…”
Section: Giardia Interactions With Intestinal Commensal Microbiotamentioning
confidence: 99%
“…However, this result must be further examined as the data was provided from 12 year-frozen samples and were taken from a study that was not designed to examine the intestinal microbiota composition [38]. The two latest studies identifying the taxa of duodenal microbiota during murine Giardia infections both use samples extracted from intestinal segments for sequencing rather than fecal samples [30, 37]. However, bacterial community analysis derived from fecal samples of non-antibiotic treated, infected mice were indistinguishable when compared to uninfected control mice [30].…”
Section: Giardia Interactions With Intestinal Commensal Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Others demonstrated increased expression of the anti‐inflammatory molecules due to inhibition of genes associated with inflammatory responses . Interestingly, Giardia alters the inflammatory markers in the intestine when presents alone and they are strongly increased in co‐infection with other pathogens . Some observations showed that Giardia infections could protect against other diarrhoeal diseases because of its immunomodulatory role.…”
Section: Discussionmentioning
confidence: 99%
“…68 Interestingly, Giardia alters the inflammatory markers in the intestine when presents alone and they are strongly increased in co-infection with other pathogens. 69 Some observations showed that Giardia infections could protect against other diarrhoeal diseases because of its immunomodulatory role. Research has demonstrated that, in some cases of Giardia infections, attenuation of pro-inflammatory leucocytes recruitment and decreased NO production occur.…”
Section: Early In Toxoplasma Infection Ifnγ Is T-cell Independent Anmentioning
confidence: 99%